Artificial Neural Networks-Based Fault Diagnosis Model for Distribution Network - Chen, Zexi; Wang, Pu; Li, Bin; Zhao, Ergang; Hao, Zhigang; Jia, Dongqiang (Distributed Generation & Alternative Energy Journal, 2023)
With many branch lines in radiant distribution networks, diagnosing faults in a distribution network is very difficult. It is of great significance to identify different types of faults quickly and accurately for the stable operation of the power grid. This research presents a fault identification model for a distribution network based on artificial neural networks. The principal component analysis first extracts features from transitory data in a distribution network. The resulting low-dimensional data is subsequently used to update the artificial neural network model. The artificial neural network may also identify the type of fault. The proposed model’s fault detection accuracy is improved over the traditional approach by examining distribution network fault data during the simulation test.